On Minimal and Vertex Minimal Dominating Graph - Basavanagoud, B.; Teredhahalli, I. M. (Journal of Informatics and Mathematical Sciences, 2009)
In this paper, we obtain the bounds on the number of edges, vertices, domatic number, and domination number of the minimal dominating graph and vertex minimal dominating graph of a graph G.